Expanded commuting in the metropolitan region of Belo Horizonte: evidence for reverse commuting - Lobo,Carlos (2015)
AbstractLarge Brazilian cities, particularly those that have experienced rapid population growth since the middle of the last century, have exhibited significant signs of population dispersion in their peripheries in recent decades. A study of the population’s spatial redistribution in the Metropolitan Region of Belo Horizonte (MRBH) confirms this finding. In the process of dispersion, the levels of urban commuting increase, and commuting becomes a relevant indicator of the degree of integration within the metropolis. This paper evaluates the current magnitude and main features of reverse commuting, as characterized by the daily displacements of the population that resides not in the periphery but rather in the core. Flows from the metropolitan core towards the peripheral municipalities are examined using sample microdata on the MRBH municipalities from the 2000 and 2010 demographic censuses by combining the variables of "municipality of residence" and "municipality of work/study." The results indicate an increase in reverse commuting in both absolute and relative terms. When this flow is compared totraditional commuting (periphery/center), the relative values are considerable. In some cases, this relationship reaches notably high values, as the case of Confins (the municipality where the international airport is located), and also municipalities that are part of a relatively old conurbation, such as Nova Lima and Betim.